Rapid separation and simultaneous quantitative determination of 13 constituents in Psoraleae Fructus by a single marker using high‐performance liquid chromatography with diode array detection. Issue 21 (26th September 2017) - Zhang, Yimin; Chen, Zhiyong; Xu, Xiaokun; Zhou, Qiang; Liu, Xiaolong; Liao, Liping; Zhang, Zijia; Wang, Zhengtao
Abstract: Psoraleae Fructus is one of the most popular traditional Chinese medicines. Coumarins, flavonoids, and meroterpenes are the main contributors to the biological activity of Psoraleae Fructus. In this study, a new method for the quality control of Psoraleae Fructus was developed, through the quantitative analysis of multicomponents by single marker with diode array detector. Thirteen components, including psoralenoside, isopsoralenoside, psoralen, isopsoralen, psoralidin, neobavaisoflavone, bavachin, corylin, isobavachalcone, corylifol A, bavachinin, bavachalcone, and bakuchiol were rapidly separated and identified within 12 min by the newly developed method. The feasibility and reliability of this method were corroborated. The method was also compared to the external standard method and detection by corona charged aerosol detector. The results of percent difference (%) and cos (θ) have shown that there were no significant differences observed between the quantitative analysis of multicomponents by single marker and external standard method analyses; psoralen and isopsoralen were undetectable with the corona charged aerosol detector due to their but the sensitivity for all the compounds except bakuchiol detected by corona charged aerosol detector are higher than those obtained by diode array detector. In addition, the newly method developed was applied to the quality evaluation of Chinese patent medicines containing Psoraleae Fructus.